A comparative analysis of intravenous infusion methods for low-resource environments - Tomobi, Oluwakemi; Avoian, Samantha; Ekwere, Ifeoma; Waghmare, Shivani; Diaban, Fatima; Davis, Gabrielle; Sy, Yacine; Ogbonna, Oluchi; Streete, Kevin; Aryee, Ebenezer; Kulasingham, Vasanthini; Sampson, John B. (Frontiers in Medicine, 2024)
Introduction: Intravenous (IV) therapy is a crucial aspect of care for the critically ill patient. Barriers to IV infusion pumps in low-resource settings include high costs, lack of access to electricity, and insufficient technical support. Inaccuracy of traditional drop-counting practices places patients at risk. By conducting a comparative assessment of IV infusion methods, we analyzed the efficacy of different devices and identified one that most effectively bridges the gap between accuracy, cost, and electricity reliance in low-resource environments. Methods: In this prospective mixed methods study, nurses, residents, and medical students used drop counting, a manual flow regulator, an infusion pump, a DripAssist, and a DripAssist with manual flow regulator to collect normal saline at goal rates of 240, 120, and 60 mL/hour. Participants' station setup time was recorded, and the amount of fluid collected in 10 minutes was recorded (in milliliters). Participants then filled out a post-trial survey to rate each method (on a scale of 1 to 5) in terms of understandability, time consumption, and operability. Costeffectiveness for use in low-resource settings was also evaluated.The manual flow regulator had the fastest setup time, was the most cost effective, and was rated as the least time consuming to use and the easiest to understand and operate. In contrast, the combination of the DripAssist and manual flow regulator was the most time consuming to use and the hardest to understand and operate.The manual flow regulator alone was the least time consuming and easiest to operate. The DripAssist/Manual flow regulator combination increases accuracy, but this combination was the most difficult to operate. In addition, the manual flow regulator was the most cost-effective. Healthcare providers can adapt these devices to their practice environments and improve the safety of rate-sensitive IV medications without significant strain on electricity, time, or personnel resources.